An interpretation center for the social use of the historical heritage of the University of San Marcos - Pinto-Bazurco Mendoza, Ricardo (2021)
From the perspective of the management of cultural heritage, the design of a space that allows the public to know the historical heritage of the National University of San Marcos is proposed. Well, it is paradoxical that the exhibition of its assets with patrimonial value, circumscribed to its rich and vast history, is an almost unknown area because it lacks an adequate physical and / or virtual space, ordered and organized for its permanent display. This heritage, as a whole, is perceived as distant and isolated objects or, simply unknown due to the lack of adequate promotion and dissemination of the important participation of the academic institution in the process of development of the cultural and national history of Peru. In this sense, it is possible to propose a new scenario through the design and development of an interpretation center that promotes the social use of the historical heritage of the UNMSM where the recipients can discover, in a didactic and tangible way, the historical meaning and heritage value of the cultural assets owned by the Dean University of America.